Using Total Worker Health (R) to Advance Worker Health and Safety - Rohlman, Diane; Kelly, Kevin M. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
It is now recognized that workplace aspects (scheduling, shift work, physically demanding work, chemical exposure) not only increase the risk of injury and illness, but also impact health behaviors (smoking, physical activity) and health outcomes (sleep disorders and fatigue, obesity, musculoskeletal disorders). In turn, ill health and chronic conditions can affect performance at work, increasing risk for injury, absenteeism, and reduced productivity. In the past few decades, programs that expand the traditional focus of occupational safety and health to consider nontraditional work-related sources of health and well-being have been shown to be more effective than programs that separately address these issues. This Total Worker Health approach has been recognized by the National Institute for Occupational Safety and Health (NIOSH) as a method for protecting the safety and health of workers, while also advancing the overall well-being of these workers by addressing work conditions. This compendium presents work from an international collection of scholars exploring the relationship between workplace factors and worker safety, health, and well-being. It provides guidance for improving the organization and design of work environments, innovative strategies for promoting worker well-being, and novel methods for exposing underlying occupational causes of chronic disease.